Study the effect of external periodic excitation on the chua’s circuit using the gyrator - Nguyen, Xuân Huy; Dong , Minh Long; Nguyen , Văn Bình; Dang , Văn Liệt (Journal of Technical Education Science, 2012)
In this paper we studied the chaotic behaviours of the Chua’s circuit using the gyrator with the external periodic excitation by the simulation and experiment. The results included of the bifurcation’s diagram, period-adding scenario, limit cycle and coexistence of multiple attractors, quasi-periodic and intermittent behaviors and equal periodic bifurcation. These results are more plentiful to compare with the previous ones